Anatomical Segmentectomy with a Hybrid VATS Approach in a Patient with Intralobar Pulmonary Sequestration after Severe Pneumonia: A Case Report - Soichi Shibuya; Toru Nakamura; Eiji Miyazaki (Georg Thieme Verlag KG, 2017)
Anatomical segmentectomy is an advantageous procedure because it spares healthy lung that has potential to show compensatory growth after lung resection and decreases the risk of air leak and residual resection, which becomes a problem in wedge resection. However, anatomical segmentectomy has not become a common procedure in pediatrics because it requires more complicated procedure than lobectomy or wedge resection, especially in patients with a history of pulmonary infection. In this case report, anatomical basal segmentectomy was safely performed with magnified vision by a hybrid video-assisted thoracic surgery (VATS) approach in a 6-year-old girl with intralobar pulmonary sequestration after severe pneumonia. The result suggests that the indications for hybrid VATS segmentectomy can expand further to include segmental lesions in children.